Rhizobiome Transplantation: A Novel Strategy beyond Single-Strain/Consortium Inoculation for Crop Improvement - Ma. del Carmen Orozco-Mosqueda; Ajay Kumar; Olubukola Oluranti Babalola; Gustavo Santoyo (Plants, 2023)
The growing human population has a greater demand for food; however, the care and preservation of nature as well as its resources must be considered when fulfilling this demand. An alternative employed in recent decades is the use and application of microbial inoculants, either individually or in consortium. The transplantation of rhizospheric microbiomes (rhizobiome) recently emerged as an additional proposal to protect crops from pathogens. In this review, rhizobiome transplantation was analyzed as an ecological alternative for increasing plant protection and crop production. The differences between single-strain/species inoculation and dual or consortium application were compared. Furthermore, the feasibility of the transplantation of other associated micro-communities, including phyllosphere and endosphere microbiomes, were evaluated. The current and future challenges surrounding rhizobiome transplantation were additionally discussed. In conclusion, rhizobiome transplantation emerges as an attractive alternative that goes beyond single/group inoculation of microbial agents; however, there is still a long way ahead before it can be applied in large-scale agriculture.